Florida H2OSAV Insights: Home Water Use in Osceola County - Nick Taylor; Kaitlin Robb Price; Bradley Spatz; Parker Johnson; Pierce Jones (EDIS)
This fact sheet provides current, basic information about residential water use in Osceola County, Florida. Written by Nick Taylor, Kaitlin Robb Price, Bradley Spatz, Parker Johnson, and Pierce Jones, and published by the UF/IFAS Department of Agricultural and Biological Engineering, November 2021.